Pengaruh Kesehatan Mental Dan Kecerdasan Emosional Terhadap Turnover Intention - Alifa Aulia Rahmi Z; Sari Octavera (CV. ITTC INDONESIA, 2025)
The phenomenon of turnover intention, or employees’ intention to leave their organization, has become a critical issue in modern human resource management, particularly among Generation Z who are increasingly dominating the workforce. This generation is characterized as dynamic, critical, and strongly oriented toward achieving balance between personal and professional life. High turnover intention has significant negative implications for organizations, including increased recruitment and training costs as well as decreased overall productivity. One factor influencing turnover intention is mental health, as employees’ psychological well-being greatly affects their loyalty and job satisfaction. Another important factor is emotional intelligence, which refers to the ability to recognize, regulate, and manage one’s own emotions as well as the emotions of others, thereby enabling employees to adapt to workplace pressures and conflicts more effectively. This study aims to analyze the influence of mental health and emotional intelligence on turnover intention among Generation Z employees. This research employed a quantitative method with a survey approach, involving 100 respondents who are alumni of Dharma Andalas University, categorized as Generation Z, and currently employed. The sampling technique used was purposive sampling, while data analysis was conducted using multiple linear regression with the assistance of SPSS. The results revealed that: (1) mental health has a negative and significant effect on turnover intention, (2) emotional intelligence has a negative and significant effect on turnover intention, and (3) mental health and emotional intelligence simultaneously exert a significant effect on turnover intention. These findings suggest that the better the employees’ mental health and the higher their emotional intelligence, the lower their intention to leave their current organization. This study provides practical implications for organizations, emphasizing the importance of providing mental health support programs such as employee wellness initiatives, as well as emotional intelligence training and development programs to reduce turnover intention among Generation Z employees.